Correction: Oleuropein down-regulated IL-1β-induced inflammation and oxidative stress in human synovial fibroblast cell line SW982. Issue 6 (31st May 2017) - Castejón, Maria Luisa; Rosillo, Maria Ángeles; Montoya, Tatiana; González-Benjumea, Alejandro; Fernández-Bolaños, Jose G.; Alarcón-de-la-Lastra, Catalina
Abstract : Correction for 'Oleuropein down-regulated IL-1β-induced inflammation and oxidative stress in human synovial fibroblast cell line SW982' by Maria Luisa Castejón, et al., Food Funct., 2017, DOI: 10.1039/c7fo00210f.